Minimising energy consumption and environmental burden of freight transport using a novel graphical decision-making tool. (October 2019) - Fan, Yee Van; Klemeš, Jiří Jaromír; Walmsley, Timothy Gordon; Perry, Simon
Abstract: This study introduces a new graphical decision-making tool to facilitate the rapid selection of transportation modes with minimum energy consumption or emissions, indicating the most sustainable transportation mode. Greenhouse gas (GHG) and air pollutants (NOx, PM and SO2 ), together with a composite price-weighted total environmental burden (TEB), are considered in the analysis. The graphical tool, which has a similar appearance to a phase diagram, presents a map of energy use (or emission) of different transportation modes based on the values of the ratio of the transportation distances (R) and the absolute load (L). A freight transportation case study (Rotterdam to Antwerp and Genova) demonstrates the construction and application of the graphical tool. For this case study, the electric train is the transport mode that offers the lowest energy consumption and minimum TEB. The graphical decision tool can also indicate the next-best solutions when one or more options (e.g. electric train) are not available. In this scenario, general cargo shipping achieves the lowest GHG emission, but heavy lorry imposes the lowest TEB. The developed tool further demonstrates the impacts of possible future fuels and technology developments on transportation selection, including renewable biodiesel and transport electrification under different grid mixes (e.g. Latvia, Sweden and EU-28). Further criteria, including economics, can be included for future study using the proposed tool as a foundation. The graphical approach transforms the transport selection problem into an easily understandable format from which arises sound solutions. Highlights: Develops a novel graphical tool for energy and environmental-friendly transportation. Introduces the concept of route distances ratio and loads as the feed-in data. Compares energy consumption, GHG and air pollutants for transport alternatives. Determines the decisive role of SO2, NOx emission and empty vehicle weight. Identifies the impact of alternatives energy sources for the transportation.